2022
DOI: 10.3389/fonc.2022.868726
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Exosomes From Cancer-Associated Mesenchymal Stem Cells Transmit TMBIM6 to Promote the Malignant Behavior of Hepatocellular Carcinoma via Activating PI3K/AKT Pathway

Abstract: ObjectiveCancer-associated mesenchymal stem cells (MSCs) regulate the progression of cancers through exosome-delivered components, while few studies are conducted on hepatocellular carcinoma (HCC). This study aimed to evaluate the effect of exosomes from HCC-associated MSCs (HCC-MSCs) on HCC cellular functions and the potential regulatory mechanism.MethodsHCC cells (Huh7 and PLC) were cultured normally or co-cultured with HCC-MSCs, HCC-MSCs plus GW4869, or HCC-MSC-derived exosomes; then mRNA sequencing and RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…TMBIM6, also named as transmembrane Bax inhibitor motif containing-6, is an inhibitor of Bax-induced apoptosis [48]. Growing evidences has indicated that TMBIM6 exert an oncogenic role in multiple cancers, including squamous cervical, non-small cell lung, breast, nasopharyngeal, hepatocellular, glioblastoma, and laryngeal squamous cell carcinoma [29,37,45,[49][50][51][52][53]. Our study implied that TMBIM6 was modified by m6A in the transcription level and interacts with IGF2BP3 and STRIP2, resulting in the stabilization of TMBIM6.…”
Section: Discussionmentioning
confidence: 99%
“…TMBIM6, also named as transmembrane Bax inhibitor motif containing-6, is an inhibitor of Bax-induced apoptosis [48]. Growing evidences has indicated that TMBIM6 exert an oncogenic role in multiple cancers, including squamous cervical, non-small cell lung, breast, nasopharyngeal, hepatocellular, glioblastoma, and laryngeal squamous cell carcinoma [29,37,45,[49][50][51][52][53]. Our study implied that TMBIM6 was modified by m6A in the transcription level and interacts with IGF2BP3 and STRIP2, resulting in the stabilization of TMBIM6.…”
Section: Discussionmentioning
confidence: 99%
“…TMBIM6, also named as transmembrane Bax inhibitor motif containing-6, is an inhibitor of Bax-induced apoptosis [47] . Growing evidences has indicated that TMBIM6 exert an oncogenic role in multiple cancers, including squamous cervical, non-small cell lung, breast, nasopharyngeal, hepatocellular, glioblastoma, and laryngeal squamous cell carcinoma [28,36,44,[48][49][50][51][52] . Our study implied that TMBIM6 was modi ed by m6A in the transcription level and interacts with IGF2BP3 and STRIP2, resulting in the stabilization of TMBIM6.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC) cells, MSC-derived exosomes increase proliferation, invasion, sphere formation ability and suppress apoptosis through TMBIM6. As a result of silencing TMBIM6, viability, sphere formation, invasion, epithelial mesenchymal transition and PI3K/AKT signaling pathway are suppressed, and apoptosis is triggered ( Shang et al, 2022 ). Adipocyte-derived exosomes differentiated from MSC in breast cancer promote cell proliferation and migration, and also inhibit apoptosis via the Hippo signaling pathway.…”
Section: Mesenchymal Stem Cell-derived Exosomes In Cancermentioning
confidence: 99%